Intrahepatic Cholestasis of Pregnancy is Associated with Gestational Diabetes Mellitus - Gulenay Gencosmanoglu Turkmen; Zehra Vural Yilmaz; Yuksel Oguz; Kadriye Yakut; Cem Yasar Sanhal; Dilek Uygur (Medical Network, 2019)
Objectıves: Intrahepatic (also known as obstetric) cholestasis of pregnancy (ICP) is one of the most frequently diagnosed conditions for pregnancy-specific hepatic disease. It has consistently been found to be related to adverse pregnancy outcomes. In recent studies, a relationship between ICP and Gestational Diabetes Mellitus (GDM) was demonstrated. However, the association between serum total BA (TBA) level in ICP and GDM is not fully understood. This study aims to evaluate the association between serum TBA levels in ICP disease with GDM. Study Desıgn: Eighty pregnant women diagnosed with ICP and eighty healthy pregnant women as normal controls were included in the study. Their clinical characteristics and laboratory test results including liver function tests, glucose challenge tests (GCT), glucose tolerance tests (GTT), and fasting and postprandial TBA levels were recorded. Cases with serum TBA levels between 12-40 µmol/L were described as mild disease, >40 µmol/L was described as severe disease. Results: The mean 50-g GCT value was significantly higher in pregnant women with ICP compared to the healthy controls (128.7±28.2, 106.6±27.0; p < 0.0001) and it was slightly higher in women with severe disease than women with mild disease (132.7±30.1, 125.5±26.5; p=0.26). The percent of GDM diagnosis with ICP disease (11.25%) was higher than in healthy pregnant women (6.25%) but the difference was not found to be statistically significant (p=0.187) and it was similar in pregnant women with mild and severe disease (11.1%, 11.4%; p=0.31). Conclusıon: Our current study demonstrated that ICP was not associated with GDM, also, we did not demonstrate a relationship of TBA level with ICP and GDM. It may be due to our study's small sample size. Further and well-designed studies with larger sample sizes are necessary to determine the relationship between GDM and ICP and also the function of TBA in the pathogenesis of GDM disease.